2004
DOI: 10.1302/0301-620x.86b5.14927
|View full text |Cite
|
Sign up to set email alerts
|

Alignment in total knee arthroplasty

Abstract: Restoration of neutral alignment of the leg is an important factor affecting the long-term results of total knee arthroplasty (TKA). Recent developments in computer-assisted surgery have focused on systems for improving TKA. In a prospective study two groups of 80 patients undergoing TKA had operations using either a computer-assisted navigation system or a conventional technique. Alignment of the leg and the orientation of components were determined on post-operative long-leg coronal and lateral films. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
155
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(168 citation statements)
references
References 19 publications
11
155
0
2
Order By: Relevance
“…An overall error of no more than 2.0 is often considered the standard for most modern computerassisted systems, 1,10,17,34 and previous studies have reported alignment errors on the order of 2 to 3 at the hip 11,20 and knee. 3,23,32 In this study, implant alignment error for the reduced stem was 1.3 AE 0.5 mm and 1.2 AE 0.4 . This can be considered to be the accuracy of the computerassisted technique.…”
Section: Discussionmentioning
confidence: 55%
“…An overall error of no more than 2.0 is often considered the standard for most modern computerassisted systems, 1,10,17,34 and previous studies have reported alignment errors on the order of 2 to 3 at the hip 11,20 and knee. 3,23,32 In this study, implant alignment error for the reduced stem was 1.3 AE 0.5 mm and 1.2 AE 0.4 . This can be considered to be the accuracy of the computerassisted technique.…”
Section: Discussionmentioning
confidence: 55%
“…Various ranges of acceptable limb alignment have been reported, but ±3° varus/valgus mechanical axis has been associated with higher success rates7,8). The postoperative limb alignment can be over ±3° varus/valgus in up to 30% of the cases after conventional TKAs9).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, to gain high flexion angle after TKA, it is necessary to reduce implant malposition. The implant malposition with conventional instrumentation in TKA can be as high as 20 %–40 %, even in major arthroplasty centers, as reported in the literatures [4, 5]. To limit implant malposition, smart tools such as navigation or patient-specific instrumentation have been developed in TKA [6, 7].…”
Section: Introductionmentioning
confidence: 99%